A practical example of recovery improvements in a bacterial oxidation plant - B. Steyn (The Southern African Institute of Mining and Metallurgy, 2009)
AngloGold Ashanti?s Obuasi Mine, in Ashanti Province, Ghana, operates a plant utilizing bacterial oxidation technology. The mineralization consists predominately of arsenopyrite with gold associated in the sulphides. The plant was commissioned in 1994, at that time was the largest BIOX® plant in the world, and has been operated by AngloGold Ashanti since 2004. The constraints identified in the plantwere the flotation capacity, BIOX® feed size and disruptions to the BIOX® process. This paper focuses on the practical steps that were followed in order to increase the recovery of the plant. The original plant design was based on a head grade of 10 g/t and an overall recovery of 86.5%. In 2007 the plant was operating at an overall recovery of 79.2% at a head grade of 5.6 g/t and this has improved to 80.6% at a head grade of 5.8 g/t during the last quarter of 2008. Additional improvement to 81.5% are expected by the end of April 2009. Improvements that have been implemented include: ?Replacement of the regrind mill ?Installation of additional float capacity ?Installation of a scavenging circuit ?Installation of a complete water treatment plant. In addition we have focused on the effect of the water circuit on the BIOX® process and the steps involved in correcting this problem. The water circuit was originally designed as an open circuit and through environmental considerations the circuit was closed towards the end of 2007. The bacteria in the BIOX® are particularly sensitive to cyanide and cannot tolerate levels above 0.05ppm (free cyanide), this required extensive modifications to the water circuit. The plant improvement project is ongoing and the current scope of work should be complete by the end of April 2009. Further research and development work is being planned, which includes a ?white rot bacteria? that can consume the preg-robbing carbon and oxidize the sulphide in a single pass.